2004
DOI: 10.17730/praa.26.2.0456r98m2pvg200g
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Youth Participatory Action Research Model to Serve LBGTQ Youth of Color

Abstract: A recent review of available research and secondary data analysis on LGTBQ (Lesbian, gay, transgender, bisexual and questioning) youth of color1 points to their struggles in coming to terms with their gender, sexual, ethnic/racial, and developmental identities. They must manage the multiple burdens of stigma, racial/ethnic prejudice and sexual discrimination, harassment and ignorance that are associated with being "non-heterosexual." For many, traditional family expectations with respect to religion, marriage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Researchers describe the experience of sexual minority youth of color facing increased stressors and safety risks (Parks, 2001;Saewyc, Skay, Bearinger, Blum, & Resnick, 1998). The literature also suggests gaps in support systems for sexual minority youth of color including families, religious institutions, and schools (Owens & Jones, 2004). However, regardless of the specific racial, ethnic, and/or cultural background of sexual minority youth, research findings clearly indicate that understanding the influence of gender roles and stereotypes is a key aspect of working with sexual minority youth (Greene, 1997;Ryan, 1999).…”
Section: Future Research Examining Risk Factors Associated With the Vmentioning
confidence: 99%
“…Researchers describe the experience of sexual minority youth of color facing increased stressors and safety risks (Parks, 2001;Saewyc, Skay, Bearinger, Blum, & Resnick, 1998). The literature also suggests gaps in support systems for sexual minority youth of color including families, religious institutions, and schools (Owens & Jones, 2004). However, regardless of the specific racial, ethnic, and/or cultural background of sexual minority youth, research findings clearly indicate that understanding the influence of gender roles and stereotypes is a key aspect of working with sexual minority youth (Greene, 1997;Ryan, 1999).…”
Section: Future Research Examining Risk Factors Associated With the Vmentioning
confidence: 99%
“…YPAR entails youth working in collaboration with adults to research social justice issues of their choosing and take action to transform unjust systems (Brion-Meisels & Alter, 2018;Cammarota, 2011;Cammarota & Fine, 2008;Lac, 2019;Rodríguez & Brown, 2009). YPAR scholarship has documented the ways that youth of Color have weighed in on a range of issues in urban schools, including inequitable access to educational resources (Mirra et al, 2015), the racist enforcement of dress codes (Welton et al, 2016), and discrimination based on race and sexuality (Owens & Jones, 2004). And, finally, scholarship and also media reports about youth organizing and activism have shown the influence and tenacity of youth of Color fighting for social justice (Ginwright, 2010;Moya, 2017).…”
Section: Youth Participation In Decision-making: Possibilities and Ob...mentioning
confidence: 99%
“…Scholarship has shown that garnering youth’s perspectives on educational policies and practices is necessary if the goal is the improvement of youth’s experiences and outcomes in education (Irizarry & Welton, 2014; Quijada Cerecer et al, 2013). Some of this research further contends that especially the youth negatively affected by structural inequities, such as youth of Color in urban settings, are those whose inclusion in school- or district-level policy decisions is essential to disrupting structural oppression as related to white supremacy, systemic racism, classism, anti-LGBTQ practices, language and religious exclusion, anti-immigrant practices, ableism, and more (see Fine, 2008; Owens & Jones, 2004; Quijada Cerecer et al, 2013). This scholarship suggests that a commitment from the field of education—including researchers and practitioners—to make space for youth involvement in decision-making in urban schools and districts would act as a lever to advance equity.…”
mentioning
confidence: 99%
“…The only thing left is for the youth and their research to be taken seriously by adults. A range of studies has illustrated the potential for social justice-oriented policy change when educational leaders heed the recommendations generated from YPAR, especially that which centers youth who face the most injustice, including youth of Color, LGTBQ youth, and/or immigrant youth (e.g., Owens & Jones, 2004; Quijada Cerecer et al, 2013). However, it is unclear whether YPAR presentations—and YPAR projects in general—compel these leaders to act.…”
mentioning
confidence: 99%